Laboratory Study of the Displacement Coalbed CH4 Process and Efficiency of CO2 and N2 Injection - Liguo Wang; Yuanping Cheng; Yongkang Wang (The Scientific World Journal)
ECBM displacement experiments are a direct way to observe the gas displacement process and efficiency by inspecting the produced gas composition and flow rate. We conducted two sets of ECBM experiments by injecting N2 and CO2 through four large parallel specimens (300×50×50 mm coal briquette). N2 or CO2 is injected at pressures of 1.5, 1.8, and 2.2 MPa and various crustal stresses. The changes in pressure along the briquette and the concentration of the gas mixture flowing out of the briquette were analyzed. Gas injection significantly enhances CBM recovery. Experimental recoveries of the original extant gas are in excess of 90% for all cases. The results show that the N2 breakthrough occurs earlier than the CO2 breakthrough. The breakthrough time of N2 is approximately 0.5 displaced volumes. Carbon dioxide, however, breaks through at approximately 2 displaced volumes. Coal can adsorb CO2, which results in a slower breakthrough time. In addition, ground stress significantly influences the displacement effect of the gas injection.